THE LABOR MARKET OF THE PROFESSIONALS OF COSTS IN PARANÁ: A STUDY ON THE DEMAND, SKILLS AND COMPETENCIES REQUIRED - Anzilago, Marcielle; Bernd, Daniele Cristina; Voese, Simone Bernardes (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
This study aimed to identify the demand, technical knowledge required as well as the skills and competence required of specialized professionals in costs in the labor market in the State of Paraná. This is a descriptive study with a qualitative approach that we used the content analysis technique to infer on the requirements stipulated in the notices on websites of jobs. The main results of this study indicate that in this segment, the vacancies more offered in the labor market are for analysts of the paranaense costs, being that the greatest demand of professionals of costs occurs in the city of Curitiba. The vacancies analyzed, 11% asked for training in Accounting Sciences. However it was observed that in about 60% of the vacancies advertised, not requisitioned training accounting or in related areas, 57.4% of the analyzed offerings do not require knowledge in a foreign language and 26% do not have announced requirements about the informatics skills into their offerings. It is concluded that the market requires the professional costs some skills and knowledge, in which the knowledge of costing methods of products, knowledge of managing costs and budgets and elaboration of accounting reports and managerial.